The expression level of TRAF1 in human gastric mucosa is related to virulence genotypes of Helicobacter pylori. (August 2014) - Wang, Fen; Bu, Guangkui; Feng, Qian; Liu, Zhiying; Xu, Canxia; Shen, Shourong; Yuan, Yi
Abstract Objective. To investigate the expression level of tumor necrosis factor receptor-associated factor 1 (TRAF1) in gastric mucosa tissue in patients infected with Helicobacter pylori (H. pylori) and to analyze the relationship between TRAF1 expression and H. pylori virulence. Methods. Gastric tissue samples were collected from patients with gastritis, atrophic gastritis, intestinal metaplasia with atypical hyperplasia, and gastric cancer. The expression level of TRAF1 in each group was analyzed by real-time polymerase chain reaction (PCR) and Western blot analysis. Virulence genotypes of H. pylori were determined by PCR. Results. Significant differences in TRAF1 mRNA levels were observed between the gastritis and gastric cancer groups, and the atrophic gastritis and gastric cancer groups (p < 0.05). Moreover, significant differences in TRAF1 protein levels were observed between the gastritis and intestinal metaplasia with atypical hyperplasia groups, between the gastritis and gastric cancer groups, and between the atrophic gastritis and gastric cancer groups (all p < 0.05). The virulence genotypes of cytotoxin-associated gene A (cagA), vacAs1, and vacAm1 were more frequent in the TRAF1 high-level group than in the TRAF1 low-level group (p < 0.05). Conclusion. Higher TARF1 expression level is associated with infection by CagA+/vacAs1+/m1+ virulent H. pylori strains and may promote the proliferation of gastric mucosal cells and induce gastric cancer.